Review on Granitic Rocks in Sumatra: Intrusion Process, Classification, Mineralization, and Potential Uses - Irzon, Ronaldo; Syaeful, Heri; Kusworo, Aries; Wahyudiono, Joko; Ngadenin (EKSPLORIUM, 2022)
Granitic rocks are widely distributed in Sumatra and surrounding areas. These granitoids are classified into several granite provinces of Southeast Asia with different intrusion processes and specific characteristics. This paper aims to review the intrusion of granitic rocks in Sumatra and describe the opportunities associated with it. Granite rocks are used to manufacture cultural heritage, works of art, and ornaments because of their weathering resistance, color diversity, and hardness characters. S-type granite intrusion in Sumatra might be associated with tin mineralization while silver-gold with the I-type. Theoretically, granite contains more REE than other igneous rocks. Mining and extraction difficulties complicate the direct REE exploitation from fresh granite. A-type granite relatively contains more REE than the other types, but this type of granite is not correlated with certain provinces. Indonesia has a tropical climate which is prone to weathering. Therefore, it is possible for REE and/or bauxite enrichments in the granite weathering horizon. Granite is assumed to be a potential source of uranium and thorium, especially for the S-type, because it is formed through the compression of sediments that can absorb these radioactive elements from the continental crust.